Development of two degree of freedom rehabilitation robot with assistive force control - Abu Ubaidah bin Shamsudin (Kulliyyah of Engineering, International Islamic University Malaysia, 2013)
Amongst the major challenges in post-stroke rehabilitation are the repetitiveness nature of rehabilitation procedure, and the accessibility of therapists for long-term treatment. In manual rehabilitation procedure, the patient is subjected to repetitive mechanical movement of the affected limb by the therapist. In one of the techniques called active-assist exercise, the subject moves his affected limb along a specified trajectory with the therapist guiding the motion. The therapist gives some assistance to the subject to complete the course if deemed necessary and the procedure repeats. The significant advantages of using robots in assisting rehabilitation are its efficiency and fatigue free. Therefore, robots need to be developed to have the capabilities of human therapist that can assess patient stroke condition and provide suitable rehabilitation therapy. This work focuses on developing a two-degree of freedom rehabilitation robotic platform for rehabilitating the upper extremity of post stroke patients. The therapy is restricted to the horizontal motion only. A new framework for the robot controller system is developed for the robotic platform. In particular, a low-level controller, which is a form of force controller is developed and a high-level controller, which is implemented as a supervisory controller is develop based on discrete event system theory. Simulation results show that the controller is capable of governing the active-assist exercise through autonomous guidance during the therapeutic procedure. In addition the assessment of the muscle condition is done through Chedoke-McMaster stroke assessment guidelines. In this study, a group of healthy subjects are chosen to participate in the experiment to study the performance of the robotic system.